Pengaruh Seni Digital Painting Kepada Start Up Business Sebagai Visual Brand - Reinaldo Indrajaya (Jurnal Vicidi, 2019)
The art of digital painting has a function as a form of visual representation from ideas and design that has been made by the artist. Nowadays, digital painting still be considered by the people as a visual art only used as an entertainment needed such as novel cover, Trading Card Game, animation, and others. Even tough, the definition of art can be used as a visual means that visualizing ideas and impression from the artist and from other people, apart from its needed for entertainment industry only. The purpose of this research is to find the effect of digital painting art as a visual brand of businesses from many industries to deliver the ideas, impression, and experiences from the brand to target market. Qualitative research methods are done by interviewing expert users and partners or extreme users, supported by doing observation to competitors and literation studies. The result of this research is digital painting can be implemented in any form, from merchandise as a brand’s promotion tools, to visual form like mascot, second element, or Intellectual Property.